Effectiveness of Targeting Food Aid to Malnourished Children Compared to Targeting All Children Under Two Years - Ruel, Marie T. (International Food Policy Research Institute, 2002)
The objective of this study is to compare two approaches to targeting donated supplementary food to young children. The study compares the effectiveness of the widely-used curative approach where targeting is based on the child's poor nutritional status to a preventive approach which targets children in poor communities solely on the basis of age and provides supplementary food to all children aged 6-23 months. Cost-effectiveness of the two targeting approaches will also be assessed.